Estudo do efeito da Alternagina-C, uma desintegrina do veneno de Bothrops alternatus,sobre a adesão de células normais e tumorais. Avaliação do seu potencial como agente anti-metastático - Terruggi, Cristina Helena Bruno (2004)
The α2β1 integrin is a major collagen receptor that plays an essential role in the normal and tumor cells adhesion to the extracellular matrix, as well as in the metastasis. Antagonists of integrins have been developed in order to provide powerful therapeutic approaches for the several types of cancer and metastasis treatment. A metalloproteinase/disintegrin was isolated, which is a specific inhibitor of the collagen type I binding to α2β1 integrin. This 55-kDa protein (Alternagin) and its disintegrin-like 30-kDa domain Alternagin-C (ALT-C) were isolated from the Bothrops alternatus a brazilian snake - venom. This disintegrin-like domain has an additional cysteine-rich domain, which is not found in RGD-disintegrins, and the RGD motif is replaced by an ECD sequence. So, the purposes of the project were (1) Evaluate the effect of ALT-C on tumor and non-tumor cell adhesion, proliferation and migration, (2) To study the effects of ECD-motif derived peptides on tumor and non-tumor cell adhesion. ALT-C inhibited the adhesion of NITH3T3, human bladder ECV-304, human cervix HeLa and breast MDA-MB-231cells to collagen type I (IC50 of 2.2, 1.66, 1.38 and 0,95µM respectively). Besides, when immobilized on plate wells, ALT-C supported the adhesion of these cell lines. ALTC did not detach cells which were previously bound to collagen type I. In the presence of collagen type I, ALT-C stimulates the migration of MDA-MB-231 cells and in greater concentrations it inhibits migration. ALT-C does not inhibit the adhesion and the migration of estrogen dependent MCF-7 cells. ALT-C also induces significant HUVEC proliferation in vivo, by up-regulating VEGF expression in human fibroblasts and endothelial cells. ALT-C also strongly activates Akt/PKB phosphorylation, a signaling event involved in endothelial survival and angiogenesis. In addition, related to the up-regulation of the VEGF´s expression, ALT-C up-regulates other growth factors expression involved in cell proliferation, such as IL-11, TGFβ, and EGR2 and 3, which are probably also involved on its positive effect on HUVEC proliferation. These biological activities of ALT-C can be useful in anti-cancer therapy experimental studies.